1995
DOI: 10.2307/3870148
|View full text |Cite
|
Sign up to set email alerts
|

A Mutation Altering Auxin Homeostasis and Plant Morphology in Arabidopsis

Abstract: Many aspects of plant development are associated with changing concentrations of the phytohormone auxin. Several stages of root formation exhibit extreme sensitivities to exogenous auxin and are correlated with shifts in endogenous auxin concentration. In an effort to elucidate mechanisms regulating development of adventitious roots, an ethyl methanesulfonate-mutagenized M2 population of Arabidopsis was screened for mutants altered in this process. A recessive nuclear mutant, rooty (rty), displayed extreme pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
117
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(126 citation statements)
references
References 0 publications
8
117
1
Order By: Relevance
“…In this assay, measurements of root and hypocotyl length indicated that the response of sur2 to auxin was not altered (data not shown) as described for the rty mutant (sur1) (King et al, 1995). The sensitivity to cytokinin was also tested by use of the same assay with increasing concentrations of benzyladenine (BA).…”
Section: Response Of Sur2 To Exogenous Auxin and Cytokininmentioning
confidence: 89%
See 3 more Smart Citations
“…In this assay, measurements of root and hypocotyl length indicated that the response of sur2 to auxin was not altered (data not shown) as described for the rty mutant (sur1) (King et al, 1995). The sensitivity to cytokinin was also tested by use of the same assay with increasing concentrations of benzyladenine (BA).…”
Section: Response Of Sur2 To Exogenous Auxin and Cytokininmentioning
confidence: 89%
“…In this case, a mutation would lead to increased levels of free IAA; however, in several transgenic lines overproducing auxin, an increase in the level of free IAA was correlated with an accumulation of conjugated auxin, indicating that de novo IAA biosynthesis is partially controlled by the level of conjugation (Klee et al, 1987;Romano et al, 1993;Sitbon et al, 1991Sitbon et al, , 1992Sitbon et al, , 1993. Similarly, all forms of auxin are higher in the sur1 mutant and it has been postulated that this mutation lies in the auxin biosynthetic pathway or a regulator of that pathway (Boerjan et al, 1995;King et al, 1995). Therefore, the hypothesis that changes in the level of auxin in the sur2 mutant result in deregulation of IAA biosynthesis appears less likely.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to subjecting plants to exogenous auxin and inhibitor treatments, the EXO-GUS gene was introduced into mutant backgrounds compromised in auxin transport (aux1-7; Bennett et al, 1996;Maher and Martindale, 1980), auxin signalling (axr1-12; Estelle and Somerville, 1987) and auxin levels (rooty, King et al, 1995). Results presented in Figure 6(c,d) show that EXO-GUS activity at the root tip in both aux1-7 and axr1-12 mutant backgrounds, respectively, is much reduced compared to that in AtEM201.…”
Section: Antagonistic Effects Of Auxin and Cytokinin On Exo Expressionmentioning
confidence: 99%